Benchmarking forest health surveillance and biosecurity activities for managing Australia's exotic forest pest and pathogen risks. Issue 1 (2nd January 2018) - Carnegie, A. J.; Lawson, S.; Wardlaw, T.; Cameron, N.; Venn, T.
ABSTRACT: A review of current forest health surveillance and biosecurity surveillance activities and programs in Australia was conducted, including a grower survey, followed by benchmarking against the New Zealand system. We define forest health surveillance (e.g. in plantations) as activities dealing with endemic or established non-indigenous pests, and biosecurity surveillance (e.g. at high risk sites at ports) as dealing with exotic pests not established in Australia. Australia has a robust biosecurity system, which includes a range of pre-border, at-border and post-border activities that aim to reduce the risk of pests and diseases arriving, entering and establishing in Australia. Although forestry has been well served pre-border and at the border, there are gaps in post-border forest biosecurity activities, largely due to the agri-centric nature of state biosecurity agencies, but also due to a reluctance by the forest industry to engage in biosecurity. New Zealand has a world-leading forest biosecurity surveillance system, largely funded by industry which is engaged directly in forest biosecurity. In contrast, while Australia has a comprehensive forest health surveillance program (funded by industry), there is minimal direct funding of forest biosecurity surveillance by industry and negligible direct engagement by industry in biosecurity. There are opportunities for industry members to be more involved in biosecurity, directly through day-to-day operations they already undertake (i.e. within their plantations), but also at a national level. Coordination of current forest health surveillance activities, including appointing a national coordinator, was identified by industry as a high priority, as was the standardisation of forest health surveillance data collection, development of a coordinated national forest biosecurity surveillance program and training of industry staff. Finally, we identified a need for involvement from other forest stakeholders in biosecurity, especially environmental agencies that manage the majority of the native forest estate. The National Forest Biosecurity Surveillance Strategy addresses these opportunities for improving forest biosecurity.